PENGARUH PERPUTARAN KAS, PIUTANG, DAN PERSEDIAAN TERHADAP PROFITABILITAS PERUSAHAAN - Bijak, Abdillah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The purpose of the research is to examine Cash Turnover, Receivable Turnover and Inventory Turnover simultaneously have a significant effect on profitability on property and real estate companies listed on the Indonesia Stock Exchange in 2015-2017. This research is a study using purposive sampling technique in determining samples that produce 34 sample companies. The analytical model used in this study is multiple linear regression models. The results of the study show that Cash Turnover, Receivable Turnover, and Inventory Turnover simultaneously affect Profitability can be seen from the significance amounting to 0.033 and Cash Turnover partially has an influence on profitability seen from the significance value of 0.004 while Receivable Turnover of the significance value is 0.609 and Inventory Turnover the significance value of 0.674 partially has no effect on Profitability.